Experience-Induced Change of Alcohol-Related Risk Perception in Patients with Alcohol Use Disorders - Klepper, Sarah; Odenwald, Michael; Rösner, Susanne; Senn, Smeralda; Menning, Hans; Pereyra-Kröll, Devi; Rockstroh, Brigitte (Frontiers in Psychology, 2017)
The role of alcohol-related risk perception for effective treatment of alcohol use disorders (AUD) is still unclear. The present study on 101 alcohol-dependent patients undergoing a ten-week AUD treatment protocol investigated the relationship between alcohol-related risk perception and alcohol use with the hypotheses that (1) risk perception changes across treatment, (2) changes vary with treatment-related experiences of abstinence / relapse indicating ‘risk reappraisal’, and (3) adjustment of perceived own vulnerability according to ‘risk reappraisal hypothesis’ predicts abstinence during follow-up. Abstinence during treatment was related to a decrease, and relapse during treatment to a slight increase in perceived own risks. Abstinence during the three-month follow-up varied with experience-induced risk reappraisal. The results show an impact of risk reappraisal on alcohol use and hence advocate a focus on risk reappraisal in AUD treatment.